FROM SUBJUGATION TO LIBERATION: THE PLIGHT OF NAMBUDIRI WOMEN AND THE REFORM MOVEMENTS IN KERALA - Santhan, Sunitha (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Namboothiri community, once the dominant Brahmin caste of Kerala, upheld a rigid patriarchal structure that severely restricted the rights and freedoms of its women. Namboothiri women, particularly the Antharjanams (women confined within the household), endured extreme social limitations, including seclusion, lack of education, and rigid marital norms. Their lives were dictated by oppressive customs, such as ill-fated marriages, widowhood asceticism, and social taboos that denied them personal agency. However, by the late 19th and early 20th centuries, Kerala witnessed significant reform movements aimed at dismantling these oppressive structures. Organizations like the Yogakshema Sabha, along with the efforts of progressive leaders and writers, played a crucial role in advocating for women’s education, social mobility, and legal rights. This article explores the transformation of Namboothiri women from a state of subjugation to active participation in societal change. It highlights key reform initiatives, the resistance faced, and the eventual impact on gender dynamics within the community.